Research on scallop shells transport of the Yantai coastal region in the Bohai Sea - Chen, Le; Zhang, Yibo; Liu, Yongzhi; Cao, Ruichen; Lv, Xianqing (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture is an important pillar of China's fisheries, with over 1 million tonnes of scallop shells produced annually. However, most of these shells are directly discarded into the sea, leading to continuous pollution of the marine and coastal environments, especially the coast of Yantai in the Bohai Sea where a large number of discarded scallop shell have accumulated. Methods To trace the fate of scallop shells in the ocean, this study established a model for the transport of scallop shells, coupling a two-dimensional tidal current model using the adjoint method with a Lagrangian particle model. By simulating nested tidal models, the distribution of tidal residual current in the Yantai coastal region was obtained. Then, a Lagrangian particle model was used to track the transport pathways of pollutants in the sea. Results Driven by the residual current calculated from the tidal model with the actual situation, possible pollutant release areas were inferred. The results of Lagrangian particle tracking experiments indicate that pollutants were released from the upstream accumulation area, specifically the area near Penglai Hulushan, confirming previous speculation. Discussion The scallop shells transport model can accurately simulate the spatiotemporal profile of scallop shells, which is helpful for managing scallop shell resources and improving the level of shell reuse.